Kewajiban Pelayanan Publik Oleh Pemerintah Daerah di Era Otonomi - Achmadi Achmadi (Anterior Jurnal, 2015)
In addressing policy and implementation of regional autonomy needs to be done real efficiency of governance is the implementation of the public service as it should be by apparatus/bureaucracy in a rational institutional network, which will be able to meet the challenges of public service in the implementation of regional autonomy for achieving good governance. Fore in order to provide the knowledge, expertise, skills and attitude to be able to perform duties in a professional office with based on personality and ethics, creating and apparatus that is capable of acting as a reformer and adhesive national unity, establishing the attitude and spirit of service-oriented services, shelter opinion and community empowerment, 1creating a common vision and mindset dynamics in performing general administration tasks and development for the realization of good governance.